A nomogram to predict residual cavity formation after thoracoscopic decortication in chronic tuberculous empyema. (11th February 2022) - Zhu, Pengfei; Xu, Xudong; Ye, Bo; Yu, Guocan; Fang, Likui; Yu, Wenfeng; Zhong, Fangming; Qiu, Xiaowei; Yang, Xin
Abstract: OBJECTIVES: The goal of this study was to develop and validate a nomogram for predicting residual cavity formation after video-assisted thoracoscopic decortication in patients with chronic tuberculous empyema (CTE). METHODS: We retrospectively analysed patients who were diagnosed and treated for CTE at our hospital from January 2017 to December 2020. We used univariable and binary logistic regression analyses to identify independent risk factors. A predictive nomogram was developed and validated for predicting the risk of residual cavity formation after video-assisted thoracoscopic decortication in patients with CTE. The receiver operating characteristic (ROC) was used to evaluate the nomogram. RESULTS: Data from 103 patients were analysed. The contact area between the lung and empyema (P = 0.001, odds ratio [OR] 1.017, 95% confidence interval [CI] 1.007–1.028), calcification (P = 0.004, OR 0.12, 95% CI 0.029–0.501) and thickness of the pleura (P = 0.02, OR 1.315, 95% CI 1.045–1.654) were risk factors for residual cavity formation after video-assisted thoracoscopic decortication. A 50% residual cavity formation rate was used as the cut-off to validate the nomogram model. The area under the ROC curve for the nomogram was 0.891 (95% CI, 0.82–0.963). The sensitivity and specificity of the nomogram were 86.67% and 82.19%, respectively. The calibration curve indicated good consistency between the predicted and actual risks. CONCLUSIONS: The preliminary nomogram could contribute to preventing postoperative residual cavity formation and making appropriate surgical decisions. Abstract : Tuberculosis (TB) is one of the most common causes of death from a single infectious pathogen, especially in developing countries [1].